Composite diaphragm and preparation method and application thereof

CN122959797APending Publication Date: 2026-10-23SHENZHEN CREATOR H2 MATERIAL CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202611243731.8
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2026-08-17
Publication Date
2026-10-23

AI Technical Summary

Technical Problem

所述复合隔膜具有低面电阻、高机械强度、优异的循环稳定性,以及具有较大的有效工作面积(离子传输面积),气泡在其表面停留时间短,还可以解决现有技术中碱性电解水制氢槽在高电流密度下因气泡屏蔽效应导致的电压升高问题

Benefits of technology

本发明提供的复合隔膜,通过控制所述复合隔膜中第一聚合物、无机材料和基底的质量比在特定范围内,能够使得所述复合隔膜兼顾低面电阻、高机械强度和优异的循环稳定性;同时,所述复合隔膜采用特定的结构设计,即控制第一表面的粗糙度在特定范围内,应用时,第一表面靠近阳极,第二表面靠近阴极,提高了复合隔膜有效工作面积,气泡在其表面停留时间短,解决了现有技术中碱性电解水制氢槽在高电流密度下因气泡屏蔽效应导致的电压升高问题,同时也有利于降低面电阻,提高复合隔膜的循环稳定性。

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
Patent Text Reader

Abstract

The application provides a composite diaphragm, a preparation method and application thereof, the composite diaphragm comprises a first polymer, an inorganic material and a substrate, the mass ratio of the first polymer, the inorganic material and the substrate is (40-75):(120-175):1; and the composite diaphragm has a first surface and a second surface arranged oppositely; the roughness Ra of the first surface is 0.5-15 mu m. The composite diaphragm has low surface resistance, high mechanical strength and excellent cycle stability, and simultaneously solves the problem of voltage rise caused by bubble shielding effect of an alkaline electrolytic water hydrogen production tank under high current density in the prior art.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] This invention belongs to the field of alkaline water electrolysis for hydrogen production technology, specifically relating to a composite membrane, its preparation method, and its application. Background Technology

[0002] Alkaline water electrolysis is one of the key technologies for green hydrogen production. Electrolysis of water in KOH solution can stably produce high-purity hydrogen and oxygen. In the alkaline water electrolysis device, the diaphragm is the core component, mainly undertaking the dual functions of physical isolation and ion conduction, which directly determines the safety, gas purity, and energy consumption level of hydrogen production.

[0003] However, existing alkaline water electrolysis membranes cannot simultaneously achieve low surface resistivity and high mechanical strength, affecting hydrogen production efficiency. Furthermore, during alkaline water electrolysis, hydrogen and oxygen bubbles are continuously generated on the electrode surface. Under low current density conditions, the bubbles can quickly detach and escape; however, under high current density conditions, the bubble generation rate increases dramatically, and a large number of bubbles adhere to and cover the electrode and membrane surfaces.

[0004] However, the shielding effect of bubbles (i.e., the aforementioned large number of bubbles adhering to and covering the surface of the electrodes and the diaphragm) not only blocks the ion transport channels and significantly reduces the effective working area of ​​the diaphragm, but also, since the bubbles themselves are insulators, they form a "cushion" layer in the electrolyte, increasing the path and resistance of ion transport between the electrodes, resulting in an increase in the voltage of the alkaline water electrolysis hydrogen production cell (referred to as the electrolyzer).

[0005] Therefore, developing a diaphragm with low surface resistivity, high mechanical strength, and the ability to solve the problem of voltage rise in electrolyzers under high current density is an urgent problem to be solved in this field. Summary of the Invention

[0006] To address the shortcomings of existing technologies, the present invention aims to provide a composite membrane, its preparation method, and its applications. The composite membrane possesses low surface resistivity, high mechanical strength, excellent cycle stability, and a large effective working area (ion transport area). Bubbles have a short residence time on its surface, and the invention also solves the voltage rise problem caused by bubble shielding effect in existing alkaline water electrolysis hydrogen production cells under high current density.

[0007] To achieve this objective, the present invention adopts the following technical solution: In a first aspect, the present invention provides a composite membrane comprising a first polymer, an inorganic material and a substrate, wherein the mass ratio of the first polymer, the inorganic material and the substrate is (40~75):(120~175):1; and the composite membrane has a first surface and a second surface disposed opposite to each other; wherein the roughness Ra of the first surface is 0.5~15μm.

[0008] In this invention, by controlling the mass ratio of the first polymer, inorganic material, and substrate in the composite membrane within a specific range, the composite membrane can achieve a balance of low surface resistivity, high mechanical strength, and excellent cycle stability. Simultaneously, the composite membrane employs a specific structural design, namely, controlling the roughness of the first surface within a specific range. During application, the first surface is close to the anode, facilitating rapid bubble detachment, while the second surface is close to the cathode, ensuring electrolyte wettability and further reducing interfacial resistance. This avoids the problem of increased electrolytic cell voltage due to bubble shielding effect at high current densities, thereby increasing the effective working area of ​​the composite membrane and improving its cycle stability.

[0009] In a second aspect, the present invention provides a method for preparing the composite separator according to the first aspect, the method comprising the following steps: (1) Provide a substrate and lay the substrate flat and fix it on one side of the polydimethylsiloxane template; (2) Prepare a coating slurry and coat the coating slurry onto a surface of the substrate away from the polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion and peeling of the polydimethylsiloxane template in sequence to obtain the composite membrane.

[0010] Thirdly, the present invention provides an alkaline water electrolysis device, the alkaline water electrolysis device comprising at least one of the following: (1) The composite diaphragm described in the first aspect; (2) The composite diaphragm prepared by the preparation method described in the second aspect.

[0011] Compared with the prior art, the beneficial effects of the present invention are as follows: The composite membrane provided by this invention, by controlling the mass ratio of the first polymer, inorganic material, and substrate within a specific range, enables the composite membrane to achieve low sheet resistance, high mechanical strength, and excellent cycle stability. Simultaneously, the composite membrane employs a specific structural design, controlling the roughness of the first surface within a specific range. In application, the first surface is close to the anode, and the second surface is close to the cathode, increasing the effective working area of ​​the composite membrane. This results in a short residence time of bubbles on its surface, solving the voltage rise problem caused by the bubble shielding effect in existing alkaline water electrolysis hydrogen production cells under high current density. It also helps reduce sheet resistance and improve the cycle stability of the composite membrane. Detailed Implementation

[0012] The technical solution of the present invention will be further illustrated below through specific embodiments. Those skilled in the art should understand that the embodiments described are merely illustrative of the present invention and should not be construed as limiting the invention in any way.

[0013] The present invention provides a composite membrane comprising a first polymer, an inorganic material and a substrate, wherein the mass ratio of the first polymer, the inorganic material and the substrate is (40~75):(120~175):1; and the composite membrane has a first surface and a second surface disposed opposite to each other; the roughness Ra of the first surface is 0.5~15μm.

[0014] In this invention, the first polymer provides strong gas barrier properties, the inorganic material provides high electrolysis efficiency, and the substrate provides mechanical strength. By controlling the mass ratio of the first polymer, inorganic material, and substrate material within the aforementioned range, a balance can be achieved between strong gas barrier properties, high electrolysis efficiency, and high mechanical strength, reducing sheet resistance and improving cycle stability. Furthermore, traditional membranes have two smooth, flat surfaces, allowing bubbles to easily and randomly accumulate. The composite membrane provided by this invention, through a specific structural design—specifically, designing the roughness of the first surface within a certain range—facilitates the rapid detachment and escape of bubbles during alkaline water electrolysis, preventing a large number of bubbles from adhering to and covering the electrode and membrane surfaces, thus helping to solve the problem of voltage rise in the electrolytic cell during electrolysis. The second surface, without special design, has a relatively low roughness and is designed as a relatively simple structure, even maintaining a flat surface. This maximizes electrolyte wetting without affecting the adhesion between the composite membrane and the electrode, increasing OH- ions. - The composite diaphragm of this invention not only has low surface resistance, high mechanical strength, and excellent cycle stability, but also improves the effective working area of ​​the composite diaphragm by placing the first surface near the anode and the second surface near the cathode during application. This results in a short residence time of bubbles on the surface, solving the problem of voltage rise caused by bubble shielding effect in alkaline water electrolysis hydrogen production cells under high current density in existing technologies.

[0015] In some specific embodiments of the present invention, the roughness of the first surface is greater than the roughness of the second surface.

[0016] In this invention, the mass ratio of the first polymer, the inorganic material, and the substrate material is (40~75):(120~175):1, wherein the specific values ​​of (40~75) can be, for example, 42, 45, 48, 50, 52, 55, 58, 60, 62, 65, 68, 70, 72, 74, or any two of these ranges; the specific values ​​of (120~175) can be, for example, 122, 125, 128, 130, 132, 135, 138, 140, 142, 145, 148, 150, 152, 155, 158, 160, 162, 165, 168, 170, 172, 174, or any two of these ranges.

[0017] In this invention, the first and second surfaces of the composite membrane, which are arranged opposite to each other, refer to the two surfaces of the composite membrane that are arranged opposite to each other in the thickness direction.

[0018] In this invention, the roughness Ra of the first surface is 0.5~15μm, for example, it can be a range of 0.5μm, 1μm, 1.5μm, 2μm, 2.5μm, 3μm, 3.5μm, 4μm, 4.5μm, 5μm, 5.5μm, 6μm, 6.5μm, 7μm, 7.5μm, 8μm, 8.5μm, 9μm, 9.5μm, 10μm, 10.5μm, 11μm, 11.5μm, 12μm, 12.5μm, 13μm, 13.5μm, 14μm, 14.5μm or any two of these, preferably 3~8μm.

[0019] In this invention, the test method for roughness Ra is as follows: the test is carried out in accordance with the standard GB / T1031-2009.

[0020] In this invention, the first surface is provided with a strip-shaped protrusion structure, which is either straight or wavy.

[0021] In this invention, the strip-shaped protrusion structure can be a continuous straight line or a wave shape along the width direction of the composite diaphragm, or it can be a continuous straight line or a wave shape along the length direction of the composite diaphragm.

[0022] It is understood that the length mentioned in this invention refers to the mechanical stretching direction and the direction of movement of the composite diaphragm, and the width refers to the direction perpendicular to the mechanical stretching direction and the direction perpendicular to the direction of movement of the diaphragm.

[0023] Preferably, the cross-sectional shape of the strip-shaped protrusion is arc-shaped, for example, it can be U-shaped.

[0024] In some specific embodiments of the present invention, the first surface satisfies at least one of the following: (a) The spacing between any two adjacent strip-shaped protrusions on the first surface is independently 30 to 100 μm, for example, it can be a range of 35 μm, 40 μm, 45 μm, 50 μm, 55 μm, 60 μm, 65 μm, 70 μm, 75 μm, 80 μm, 85 μm, 90 μm, 95 μm or any two of these.

[0025] In this invention, the spacing between any two adjacent strip-shaped protrusions on the first surface is within the aforementioned range, which helps to further reduce the voltage of the electrolytic cell.

[0026] (b) The width of the strip-shaped protrusions in the first surface is 1 to 50 μm, for example, it can be a range of 2 μm, 5 μm, 8 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 28 μm, 30 μm, 32 μm, 35 μm, 38 μm, 40 μm, 42 μm, 45 μm, 48 μm or any two of these.

[0027] (c) The height of the strip-shaped protrusions in the first surface is 10~50μm, for example, it can be a range of 12μm, 15μm, 18μm, 20μm, 22μm, 25μm, 28μm, 30μm, 32μm, 35μm, 38μm, 40μm, 42μm, 45μm, 48μm or any two of these.

[0028] (d) The strip-shaped protrusions in the first surface are wavy, with the distance between the crests and troughs being 20~100μm.

[0029] In this invention, the first surface is designed as an array structure with strip-shaped protrusions, which can actively guide bubbles and provide them with high points. Driven by hydrophobic forces, the bubbles tend to move directionally towards the high points (such as crests) of the structure. During the movement, small bubbles will merge into large bubbles. When the buoyancy is large enough, they will quickly detach from the surface of the composite membrane, avoiding the shielding effect of the bubbles. At the same time, it can also increase the effective working area of ​​the composite membrane. Even when there are bubbles covering the surface, the covered area is mainly the "crests", while the "troughs" can still maintain ion transport, thereby reducing the voltage of the electrolyzer under high current density.

[0030] In this invention, the width, height, and spacing between the peaks and troughs of the strip-shaped protrusions on the first surface are within the above-mentioned range, which helps to further reduce the electrolytic cell voltage, improve cycle stability, and ensure a low surface resistance.

[0031] In this invention, the spacing, height, width, and the spacing between the crests and troughs of the strip-shaped protrusions on the first surface can also be tested using a confocal microscope (purchased from Keyence).

[0032] In some specific embodiments of the present invention, the substrate is a sulfonated substrate, and the degree of sulfonation of the sulfonated substrate is 5-15%, for example, it can be a range of 5.5%, 6%, 6.5%, 7%, 7.5%, 8%, 8.5%, 9%, 9.5%, 10%, 10.5%, 11%, 11.5%, 12%, 12.5%, 13%, 13.5%, 14%, 14.5%, or any combination thereof.

[0033] The method for testing the degree of sulfonation described in this invention is as follows: Take 0.2 g of dried substrate fiber and place it in 50 mL of 2 mol / L NaCl solution, shake at 40°C for 48 hours; take the entire solution and titrate it with 0.01 mol / L NaOH standard solution using phenolphthalein as an indicator. Ion exchange capacity (IEC) = (C × V) / m, where C is the NaOH concentration (mol / L), V is the volume consumed (mL), m is the mass of substrate fiber (g), and degree of sulfonation (%) = 100 × 10⁸ × IEC / (1000 - 80 × IEC).

[0034] In this invention, the composite membrane includes a substrate and a coating layer disposed on at least one surface of the substrate; the coating layer comprises a first polymer and an inorganic material; this invention uses a sulfonated substrate, that is, by sulfonation treatment, sulfonic acid groups are grafted onto the surface of the substrate, which can control the quality of the substrate and increase the bonding force between the substrate and the coating layer, ensuring both low sheet resistance and high mechanical strength; if the degree of sulfonation is too high, the composite membrane will be too brittle and have poor mechanical properties; if the degree of sulfonation is too low, the performance will not be significantly improved, and the sheet resistance and electrolytic cell voltage will increase.

[0035] In some specific embodiments of the present invention, the density of the substrate is 1.3~1.36 g / cm³. 3 For example, it can be 1.31 g / cm³ 3 1.32 g / cm 3 1.33 g / cm 3 1.34 g / cm 3 1.35 g / cm 3 Or the range between any two of them.

[0036] In some specific embodiments of the present invention, the tensile elongation of the substrate is 10-50%, for example, it can be 15%, 20%, 25%, 30%, 35%, 40%, 45% or any two of these ranges.

[0037] In some specific embodiments of the present invention, the tensile modulus of the substrate is 1000~3000 kgf / cm². 2 For example, it can be 1200 kgf / cm 2 1500 kgf / cm 2 1800 kgf / cm 2 2000 kgf / cm 2 2200 kgf / cm 2 2500 kgf / cm 2 2800 kgf / cm 2 Or the range between any two of them.

[0038] In this invention, the tensile elongation and tensile modulus of the substrate are within the above-mentioned range, which is beneficial to achieving both high tensile strength and excellent cyclic stability.

[0039] In this invention, the test methods for the tensile elongation and tensile modulus of the substrate are GB / T 1040.3-2006.

[0040] In some specific embodiments of the present invention, the thickness of the substrate is 240~300μm, for example, it can be 250μm, 260μm, 270μm, 280μm, 290μm, etc.

[0041] In this invention, controlling the substrate thickness within the above-mentioned range is beneficial for the composite membrane to balance mechanical strength and good ion conductivity.

[0042] Preferably, the first polymer includes at least one of polysulfone, polyethersulfone, polyphenylene sulfone, and polyetheretherketone.

[0043] Preferably, the inorganic material includes at least one of zirconium dioxide, titanium dioxide, barium sulfate, and barium zirconate.

[0044] In this invention, the size of the inorganic material is not specifically limited; for example, the particle size of the inorganic material can be 10~200nm, more preferably 30~100nm.

[0045] Preferably, the substrate comprises at least one selected from polyphenylene sulfide (PPS), polypropylene (PP), polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, and polyethylene naphthalate, more preferably polyphenylene sulfide.

[0046] In some specific embodiments of the present invention, the substrate is a mesh substrate, and the mesh count of the substrate is 40 to 60 mesh, for example, it can be 45 mesh, 50 mesh, 55 mesh or any combination thereof.

[0047] Preferably, the thickness of the composite membrane is 390~520μm, for example, it can be a range of 400μm, 420μm, 440μm, 460μm, 480μm, 500μm or any combination thereof.

[0048] In this invention, the porosity of the composite membrane is 50-75%, for example, it can be a range of 55%, 60%, 65%, 70%, or any two of these values.

[0049] The present invention also provides a method for preparing the composite membrane according to the first aspect, the method comprising the following steps: (1) Provide a substrate and lay the substrate flat and fix it on one side of the polydimethylsiloxane template; (2) Prepare a coating slurry and coat the coating slurry onto a surface of the substrate away from the polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion and peeling of the polydimethylsiloxane template in sequence to obtain the composite membrane.

[0050] In this invention, the side of the polydimethylsiloxane template that is peeled off is the first surface, and the opposite surface is the second surface, which is not treated in any way.

[0051] In this invention, the preparation method utilizes templates with different structures combined with specific processes to obtain a composite diaphragm with a specific structure. The spacing, width, height, and peak-to-trough spacing of the protrusions on the surface of the composite diaphragm can be achieved by using templates with different protrusion spacing, width, height, and peak-to-trough spacing.

[0052] In this invention, the preparation method of the polydimethylsiloxane (PDMS) template is a casting molding method. Specifically, PDMS reagent is poured into a master mold sculpted using photolithography. After complete curing, demolding yields a soft PDMS mold, thus obtaining the polydimethylsiloxane (PDMS) template. The PDMS reagent is Sylgard 184 silicone rubber manufactured by Dow Corning, which is a mixture of vinyl-terminated polydimethylsiloxane, a curing agent (containing hydrogen-containing silicone oil crosslinking agent and platinum catalyst), and a defoamer at a mass ratio of 89:10:1. The prepolymer is then placed in a vacuum (≤-0.09 MPa) for 5-15 minutes to remove micro-bubbles. Finally, it is poured into the master mold and allowed to stand at room temperature for 3-6 hours, followed by heat curing in a 60-75°C oven for 1-2 hours. After curing, it is allowed to cool naturally to room temperature before demolding, yielding the polydimethylsiloxane template with the corresponding structure described in this invention.

[0053] In some specific embodiments of the present invention, the coating slurry comprises, by weight percentage, 5-15% of a first polymer (e.g., a range of 6%, 7%, 8%, 9%, 10%, 11%, 12%, 13%, 14%, or any two thereof), 20-40% of inorganic material (e.g., a range of 22%, 24%, 26%, 28%, 30%, 32%, 34%, 36%, 38%, or any two thereof), 0.5-2% of a second polymer (e.g., a range of 0.6%, 0.8%, 1%, 1.2%, 1.4%, 1.6%, 1.8%, or any two thereof), and 45-70% of organic solvent (e.g., a range of 46%, 50%, 55%, 60%, 65%, or any two thereof).

[0054] In this invention, the solid content of the coating slurry is 30-55%, for example, it can be a range of 35%, 40%, 45%, 50% or any two of these.

[0055] The present invention does not particularly limit the type of the second polymer, as long as it meets the conventional application in the art. For example, the second polymer includes a hydrophilic polymer, preferably at least one of polyvinylpyrrolidone, polyvinyl alcohol, and polypropylene glycol.

[0056] In this invention, the addition of a second polymer helps to create more uniform pores.

[0057] The present invention does not particularly limit the type of organic solvent, as long as it can dissolve the materials of the first coating layer and the second coating layer. For example, the organic solvent includes at least one of N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and diethyl sulfoxide.

[0058] In this invention, the preparation method of the coating slurry is as follows: a first polymer and an inorganic material are mixed and stirred with an organic solvent, and then a second polymer is added and stirred to obtain the slurry.

[0059] Preferably, at 25°C, the viscosity of the coating slurry is 3000~10000 cp, for example, it can be a range of 3000 cp, 4000 cp, 5000 cp, 6000 cp, 7000 cp, 8000 cp, 10000 cp or any two of these values.

[0060] In this invention, step (1) further includes the step of sulfonating the substrate.

[0061] Preferably, the reagent for the sulfonation treatment in step (1) includes fuming sulfuric acid.

[0062] Preferably, the mass ratio of the substrate to the volume of fuming sulfuric acid is 1g:(4~6)mL, wherein the specific value of (4~6)mL can be, for example, 4.2 mL, 4.4 mL, 4.6 mL, 4.8 mL, 5 mL, 5.2 mL, 5.4 mL, 5.6 mL, 5.8 mL or any combination thereof.

[0063] Preferably, based on the mass of the fuming sulfuric acid as 100%, the mass percentage of SO3 in the fuming sulfuric acid is 15-25%, for example, it can be a range of 16%, 18%, 20%, 22%, 24%, or any two of these.

[0064] In this invention, fuming sulfuric acid with different SO3 mass percentages can be purchased commercially; it can also be prepared by adding concentrated sulfuric acid or by using fuming sulfuric acid with different SO3 mass percentages.

[0065] Preferably, the sulfonation temperature in step (1) is 15~25℃, for example, it can be a range of 16℃, 17℃, 18℃, 19℃, 20℃, 21℃, 22℃, 23℃, 24℃ or any two of these; the sulfonation time is 0.2~0.6h, for example, it can be a range of 0.25h, 0.3h, 0.35h, 0.4h, 0.45h, 0.5h, 0.55h or any two of these.

[0066] In this invention, the sulfonation process includes placing the substrate in a closed nitrogen circulating hot air drying system for dehydration and drying to avoid violent side reactions between fuming sulfuric acid and moisture, which would affect the degree of sulfonation.

[0067] In this invention, the sulfonation treatment includes sequentially feeding the substrate into a first treatment tank, a second treatment tank, a third treatment tank, and a fourth treatment tank for processing. The first treatment tank contains fuming sulfuric acid; the temperature of the first treatment tank is 15~25°C, and the time in the first treatment tank is 0.2~0.6 hours (i.e., sulfonation temperature and time); the second and third treatment tanks each independently contain water; the temperatures of the second and third treatment tanks each independently are 5~10°C, for example, 6°C, 7°C, 8°C, 9°C, or any combination thereof; the second and third treatment tanks are used to rapidly terminate the reaction; the fourth treatment tank contains water; the temperature of the fourth treatment tank is 25~30°C, for example, 26°C, 27°C, 28°C, 29°C, or any combination thereof; the total time in the second, third, and fourth treatment tanks is 1~3 hours; after treatment in the fourth treatment tank, the substrate is dried to obtain the sulfonated substrate.

[0068] It is understood that the substrate is sulfonated in the first treatment tank, and then the sulfonated substrate is quenched at low temperature in the second water tank to terminate or reduce the sulfonation reaction rate; the sulfate ions on the substrate are further removed in the third water tank; and the substrate is finally cleaned and dried in the fourth water tank to obtain the sulfonated substrate.

[0069] In some specific embodiments of the present invention, the coating speed in step (2) is 0.5~10 m / min, for example, it can be a range of 1 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min or any combination thereof.

[0070] In this invention, by controlling the viscosity of the slurry and the coating speed within the above-mentioned range, the penetration rate of the slurry on the grid substrate can be controlled, and the surface roughness Ra of the first surface can be further adjusted.

[0071] Preferably, the pre-evaporation temperature in step (2) is 50~110℃, for example, it can be a range of 55℃, 60℃, 65℃, 70℃, 75℃, 80℃, 85℃, 90℃, 95℃, 100℃, 105℃ or any two of these; the time is 1~5min, for example, it can be a range of 2min, 3min, 4min or any two of these.

[0072] It is understood that the phase transformation in step (2) includes immersing the pre-evaporated substrate in a non-solvent bath for phase transformation; the non-solvent bath includes a non-solvent.

[0073] The present invention does not specifically limit the type of non-solvent, as long as it can achieve phase transformation. For example, the non-solvent used in the phase transformation in step (2) includes at least one of water, methanol, ethanol, n-propanol, isopropanol, and n-butanol.

[0074] Preferably, the phase transition time in step (2) is 0.5 to 3 hours, for example, it can be a range of 1 hour, 1.5 hours, 2 hours, 2.5 hours or any two of these.

[0075] The present invention does not impose a particular limitation on the phase transition temperature, but in order to improve the consistency of the composite membrane, the phase transition temperature in step (2) can be 30~90℃, specifically 40℃, 50℃, 60℃, 70℃, 80℃ or any two of these ranges.

[0076] Preferably, the peeling rate of the polydimethylsiloxane template in step (2) is 1~10 m / min, for example, it can be a range of 1.5 m / min, 2 m / min, 3 m / min, 4 m / min, 5 m / min, 6 m / min, 7 m / min, 8 m / min, 9 m / min or any combination thereof; the peeling force is 1~5 N / cm. 2 For example, it can be 1.2 N / cm 2 1.5 N / cm 2 1.8 N / cm 2 2 N / cm 2 2.2 N / cm 2 2.5 N / cm 2 2.8 N / cm 2 3 N / cm 2 3.2 N / cm 2 3.5 N / cm 2 3.8 N / cm 2 4 N / cm 2 4.2 N / cm 2 4.5 N / cm 2 4.8 N / cm 2 Or a range of values ​​consisting of any two of them.

[0077] In this invention, controlling the peeling rate and peeling force within the above-mentioned range is beneficial for obtaining a first surface with a specific roughness.

[0078] The present invention also provides an alkaline water electrolysis device, wherein the alkaline water electrolysis device comprises at least one of the following: (1) The composite diaphragm described in the first aspect; (2) The composite diaphragm prepared by the preparation method described in the second aspect.

[0079] Preferably, the alkaline water electrolysis device includes an electrolysis cell, which includes an anode, the composite membrane described in the first aspect, and a cathode arranged sequentially; the first surface of the composite membrane is attached to the anode, and the second surface is attached to the cathode.

[0080] The numerical range described in this invention includes not only the point values ​​listed above, but also any point values ​​within the numerical ranges not listed above. Due to space limitations and for the sake of brevity, this invention will not exhaustively list all the specific point values ​​included in the range.

[0081] The technical solutions provided by the present invention will be clearly and completely described below with reference to embodiments and comparative examples. Obviously, the specific embodiments described are only some embodiments of the present invention, and not all embodiments.

[0082] All materials used in this invention are commercially available or prepared using conventional methods; unless otherwise specified, the materials used in this invention are as follows: Polyphenylene sulfide network substrate 1: 260 μm thick, 50 mesh, density 1.33 g / cm³ 3 The elongation at break is 25%, and the tensile modulus is 2000 kgf / cm². 2 Purchased from Ryton PPS by Saifa Filtration Technology (Suzhou) Co., Ltd.

[0083] Polyphenylene sulfide network substrate 2: 260 μm thick, 50 mesh, density 1.3 g / cm³ 3 The elongation at break is 10%, and the tensile modulus is 1100 kgf / cm². 2 The Ryton PPS was purchased from Saifa Filtration Technology Co., Ltd.

[0084] Polyphenylene sulfide network substrate 3: 260 μm thick, 50 mesh, density 1.36 g / cm³ 3 The elongation at break is 50%, and the tensile modulus is 2800 kgf / cm². 2 The PPS mesh was purchased from Shanghai Guangshun Machinery Co., Ltd.

[0085] Polyphenylene sulfide network substrate 4: 260 μm thick, 50 mesh, density 1.33 g / cm³ 3 The elongation at break is 5%, and the tensile modulus is 3500 kgf / cm². 2 The PPS mesh was purchased from Shanghai Guangshun Machinery Co., Ltd.

[0086] Polyphenylene sulfide network substrate 5: thickness 260 μm, mesh size 50, density 1.33 g / cm³ 3 The elongation at break is 60%, and the tensile modulus is 500 kgf / cm². 2 The PPS mesh was purchased from Shanghai Haifan Filter Material Co., Ltd.

[0087] Polysulfone: Purchased from Wharton Technology Corporation, VG2000.

[0088] Polyetheretherketone (PEEK): Purchased from Solvay (KetaSpire® KT-881).

[0089] Polyethersulfone: Purchased from BASF Ultrason® E 2010.

[0090] Polyvinylpyrrolidone: K90 purchased from Shanghai Aladdin Biochemical Technology Co., Ltd.

[0091] Zirconia: VK-R30 purchased from Xuancheng Jingrui New Materials Co., Ltd.

[0092] Barium sulfate: purchased from Shenzhou Jiaxin Chemical Co., Ltd. (JX80).

[0093] Example 1 This embodiment provides a composite membrane, which consists of a sulfonated polyphenylene sulfide (PPS) mesh substrate and a coating layer disposed on one surface of the PPS mesh substrate; the coating layer is composed of polysulfone and zirconium dioxide; the mass ratio of polysulfone, zirconium dioxide and sulfonated PPS mesh substrate is 72.5:150:1.

[0094] The side of the coating layer away from the sulfonated polyphenylene sulfide mesh substrate is the first surface. The roughness Ra of the first surface is 5 μm. The first surface is distributed with strip-shaped protrusions. The strip-shaped protrusions are wavy along the length of the composite membrane. The cross-sectional shape of the strip-shaped protrusions is arc-shaped. The distance between any two adjacent strip-shaped protrusions is 60 μm. The width of the strip-shaped protrusions is 25 μm and the height is 30 μm. The distance between the crest and trough is 50 μm.

[0095] The sulfonated polyphenylene sulfide network substrate is obtained by sulfonating polyphenylene sulfide network substrate 1, with a sulfonation degree of 10%; the thickness of the composite membrane is 420 μm.

[0096] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) The polyphenylene sulfide network substrate 1 is sequentially fed into the first treatment tank, the second treatment tank, the third treatment tank and the fourth treatment tank for treatment, and dried at 60°C to obtain the sulfonated polyphenylene sulfide network substrate; wherein, the first treatment tank contains fuming sulfuric acid, the mass-volume ratio of the polyphenylene sulfide network substrate 1 to the fuming sulfuric acid is 1g:5mL, and the mass percentage of free SO3 in the fuming sulfuric acid is 20%; the temperature of the first treatment tank is 20°C (the temperature of sulfonation treatment), and the time in the first treatment tank is 0.5h (the time of sulfonation treatment); the second treatment tank, the third treatment tank and the fourth treatment tank each contain water independently; the temperature of the second treatment tank and the third treatment tank each is 5°C independently, and the temperature of the fourth treatment tank is 25°C.

[0097] (2) Mix 12% polysulfone, 25% zirconium dioxide, 1% polyvinylpyrrolidone and 62% N-methylpyrrolidone evenly by mass percentage to obtain a coating slurry with a viscosity of 6000cp (25℃); (3) Fix the customized polydimethylsiloxane template with the corresponding structure, and lay the substrate flat on one side of the polydimethylsiloxane template. Control the width of the slit to the corresponding membrane thickness. Then, apply the coating slurry to the surface of the substrate away from the polydimethylsiloxane template at a speed of 5 m / min. After pre-evaporation at 80°C for 3 min, immerse it in a non-solvent bath containing water for phase inversion for 2 h. Peel at a rate of 5 m / min and a peeling force of 2.5 N / cm. 2 The polydimethyloxane template was peeled off under certain conditions to obtain the composite membrane.

[0098] Example 2 This embodiment provides a composite membrane, which consists of a sulfonated polyphenylene sulfide network substrate and a coating layer disposed on one surface of the sulfonated polyphenylene sulfide network substrate; the coating layer is composed of polyether ether ketone and barium sulfate; the mass ratio of polyether ether ketone, barium sulfate and sulfonated polyphenylene sulfide network substrate is 42.5:170:1.

[0099] The side of the coating layer away from the sulfonated polyphenylene sulfide mesh substrate is the first surface. The roughness Ra of the first surface is 4 μm. The first surface is distributed with strip-shaped protrusions. The strip-shaped protrusions are wavy along the length of the composite membrane. The cross-sectional shape of the strip-shaped protrusions is arc-shaped. The distance between any two adjacent strip-shaped protrusions is 30 μm. The width of the strip-shaped protrusions is 45 μm and the height is 10 μm. The distance between the crest and trough is 20 μm.

[0100] The sulfonated polyphenylene sulfide network substrate is obtained by sulfonating polyphenylene sulfide network substrate 2, with a sulfonation degree of 5%; the thickness of the composite membrane is 500 μm.

[0101] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) The polyphenylene sulfide network substrate 2 is sequentially fed into the first treatment tank, the second treatment tank, the third treatment tank and the fourth treatment tank for treatment, and dried at 60°C to obtain the sulfonated polyphenylene sulfide network substrate; wherein, the first treatment tank contains fuming sulfuric acid, the mass-volume ratio of the polyphenylene sulfide network substrate 2 to the fuming sulfuric acid is 1g:4mL, and the mass percentage of free SO3 in the fuming sulfuric acid is 15%; the temperature of the first treatment tank is 15°C (the temperature of sulfonation treatment), and the time in the first treatment tank is 0.3h (the time of sulfonation treatment); the second treatment tank, the third treatment tank and the fourth treatment tank each contain water independently; the temperature of the second treatment tank and the third treatment tank each is 10°C independently, and the temperature of the fourth treatment tank is 30°C.

[0102] (2) Mix 6% polyetheretherketone, 24% barium sulfate, 2% polyvinylpyrrolidone and 68% N-methylpyrrolidone evenly by mass percentage to obtain a coating slurry with a viscosity of 3000cp (25℃); (3) Fix the customized polydimethylsiloxane template with the corresponding structure, and lay the sulfonated polyphenylene sulfide mesh substrate on one side of the polydimethylsiloxane template. Control the width of the slits to the corresponding membrane thickness. Then, apply the coating slurry to a surface of the substrate away from the polydimethylsiloxane template at a speed of 2 m / min. After pre-evaporation at 50°C for 5 min, immerse it in a non-solvent bath containing water for phase inversion for 3 h. Peel at a rate of 1 m / min and a peeling force of 1 N / cm. 2 The polydimethyloxane template was peeled off under certain conditions to obtain the composite membrane.

[0103] Example 3 This embodiment provides a composite membrane, which consists of a sulfonated polyphenylene sulfide (PPS) mesh substrate and a coating layer disposed on one surface of the PPS mesh substrate; the coating layer is composed of polyethersulfone and zirconium dioxide; the mass ratio of polyethersulfone, zirconium dioxide and sulfonated PPS mesh substrate is 60:120:1.

[0104] The side of the coating layer away from the sulfonated polyphenylene sulfide mesh substrate is the first surface. The roughness Ra of the first surface is 8 μm. The first surface is distributed with strip-shaped protrusions. The strip-shaped protrusions are wavy along the length of the composite membrane. The cross-sectional shape of the strip-shaped protrusions is arc-shaped. The distance between any two adjacent strip-shaped protrusions is 90 μm. The width of the strip-shaped protrusions is 2 μm and the height is 50 μm. The distance between the crest and trough is 45 μm.

[0105] The sulfonated polyphenylene sulfide network substrate is obtained by sulfonating polyphenylene sulfide network substrate 3, with a sulfonation degree of 15%; the thickness of the composite membrane is 390 μm.

[0106] This embodiment provides a method for preparing the composite separator, specifically including the following steps: (1) The polyphenylene sulfide network substrate 3 is sequentially fed into the first treatment tank, the second treatment tank, the third treatment tank and the fourth treatment tank for treatment, and dried at 60°C to obtain the sulfonated polyphenylene sulfide network substrate; wherein, the first treatment tank contains fuming sulfuric acid, the mass-volume ratio of the polyphenylene sulfide network substrate 3 to the fuming sulfuric acid is 1g:6mL, and the mass percentage of free SO3 in the fuming sulfuric acid is 25%; the temperature of the first treatment tank is 25°C (the temperature of sulfonation treatment), and the time in the first treatment tank is 0.6h (the time of sulfonation treatment); the second treatment tank, the third treatment tank and the fourth treatment tank each contain water independently; the temperature of the second treatment tank and the third treatment tank are each 5°C independently, and the temperature of the fourth treatment tank is 25°C.

[0107] (2) Mix 10% polyethersulfone, 20% zirconium dioxide, 0.5% polyvinylpyrrolidone and 69.5% N-methylpyrrolidone evenly by mass percentage to obtain a coating slurry with a viscosity of 5000cp (25℃); (2) Fix the customized polydimethylsiloxane template with the corresponding structure, and lay the sulfonated polyphenylene sulfide mesh substrate on one side of the polydimethylsiloxane template. Control the width of the slit to the corresponding membrane thickness. Then, apply the coating slurry to one surface of the sulfonated polyphenylene sulfide mesh substrate away from the polydimethylsiloxane template at a speed of 9 m / min. After pre-evaporation at 110°C for 1 min, immerse it in a non-solvent bath containing water for phase inversion for 1 h. Peel at a peeling rate of 10 m / min and a peeling force of 5 N / cm. 2 The polydimethyloxane template was peeled off under certain conditions to obtain the composite membrane.

[0108] Example 4 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the roughness Ra of the first surface is 4 μm, the strip-shaped protrusions on the first surface are straight along the length of the composite membrane, and the cross-sectional shape of the strip-shaped protrusions is arc-shaped; the distance between any two adjacent strip-shaped protrusions is 60 μm, the width of the strip-shaped protrusions is 25 μm, and the height is 30 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and other materials, structural parameters, and preparation methods are the same as in Embodiment 1.

[0109] Example 5 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the spacing between any two adjacent strip-shaped protrusions on the first surface is 10 μm, and the roughness of the first surface is 8.5 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0110] Example 6 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the spacing between any two adjacent strip-shaped protrusions on the first surface is 120 μm, and the roughness of the first surface is 4.5 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0111] Example 7 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the width of the strip-shaped protrusions on the first surface is 0.5 μm and the roughness of the first surface is 7.5 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0112] Example 8 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the width of the strip-shaped protrusions on the first surface is 55 μm and the roughness of the first surface is 3.5 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0113] Example 9 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the height of the strip-shaped protrusions on the first surface is 5 μm and the roughness of the first surface is 4 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0114] Example 10 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the height of the strip-shaped protrusions on the first surface is 55 μm and the roughness of the first surface is 7 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0115] Example 11 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the distance between the peaks and troughs of the strip-shaped protrusions on the first surface is 120 μm, and the roughness of the first surface is 4.5 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0116] Example 12 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the distance between the peaks and troughs of the strip-shaped protrusions on the first surface is 10 μm, and the roughness of the first surface is 6 μm; the preparation method uses a polydimethylsiloxane template with a corresponding structure, and the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0117] Example 13 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the degree of sulfonation of the sulfonated polyphenylene sulfide network substrate is 4%, and the mass ratio of polysulfone, zirconium dioxide and sulfonated polyphenylene sulfide network substrate is 72.5:150:0.94 (i.e. 77.1:159.6:1). In the preparation method, the mass-volume ratio of the polyphenylene sulfide network substrate to fuming sulfuric acid is 1g:3mL, and the mass percentage of free SO3 in the fuming sulfuric acid is 10%. Other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0118] Example 14 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the degree of sulfonation of the sulfonated polyphenylene sulfide network substrate is 20%, and the mass ratio of polysulfone, zirconium dioxide and sulfonated polyphenylene sulfide network substrate is 72.5:150:1.1 (i.e. 65.9:136.4:1). In the preparation method, the mass-volume ratio of the polyphenylene sulfide network substrate to fuming sulfuric acid is 1g:7mL, and the mass percentage of free SO3 in the fuming sulfuric acid is 30%. Other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0119] Example 15 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the degree of sulfonation of the sulfonated polyphenylene sulfide network substrate is 2%, and the mass ratio of polysulfone, zirconium dioxide and sulfonated polyphenylene sulfide network substrate is 72.5:150:0.9 (i.e. 80.6:166.7:1); in the preparation method, the mass percentage of free SO3 in the fuming sulfuric acid is 0%, and other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0120] Example 16 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the polyphenylene sulfide mesh substrate 1 is replaced with an equal mass of polyphenylene sulfide mesh substrate 4. In the preparation method, other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0121] Example 17 This embodiment provides a composite membrane, which differs from Embodiment 1 in that the polyphenylene sulfide mesh substrate 1 is replaced with an equal mass of polyphenylene sulfide mesh substrate 5, while the other materials, structural parameters and preparation methods are the same as in Embodiment 1.

[0122] Comparative Example 1 This comparative example provides a composite membrane, which differs from Example 1 in that the roughness Ra of the first surface is 0.4 μm. In the preparation method, step (3) does not use a polydimethylsiloxane template, but directly coats the coating slurry onto one surface of the substrate. Other materials, structural parameters and preparation methods are the same as in Example 1.

[0123] Comparative Example 2 This comparative example provides a composite diaphragm, which differs from Example 1 in that the roughness Ra of the first surface is 15.5 μm, and in the preparation method, the coating slurry speed is adjusted to 20 m / min, the peeling rate is 15 m / min, and the peeling force is 10 N / cm. 2 Other materials, structural parameters, and preparation methods are the same as in Example 1.

[0124] Comparative Example 3 This comparative example provides a composite membrane, which differs from Example 1 in that the content of polysulfone and zirconium dioxide is adjusted so that the mass ratio of polysulfone, zirconium dioxide and sulfonated polyphenylene sulfide network substrate is 30:62.1:1. In the preparation method, 11% polysulfone, 23% zirconium dioxide, 4% polyvinylpyrrolidone and 62% N-methylpyrrolidone are mixed evenly by mass percentage to obtain a coating slurry with a viscosity of 6000cp (25°C). Other materials, structural parameters and preparation methods are the same as in Example 1.

[0125] Comparative Example 4 This comparative example provides a composite membrane, which differs from Example 1 in that the content of polysulfone and zirconium dioxide is adjusted so that the mass ratio of polysulfone, zirconium dioxide and sulfonated polyphenylene sulfide network substrate is 90:186.2:1. In the preparation method, 13% polysulfone, 26.5% zirconium dioxide, 0.5% polyvinylpyrrolidone and 60% N-methylpyrrolidone are mixed evenly by mass percentage to obtain a coating slurry with a viscosity of 6000cp (25°C); other materials, structural parameters and preparation methods are the same as in Example 1.

[0126] Performance testing (1) Tensile strength: Tested in accordance with GB / T 1040.3-2006.

[0127] (2) Sheet resistance: Four sheet samples with a diameter of 4 cm were cut from the flat area of ​​the composite diaphragm. The samples were immersed in 30% KOH solution for 24 hours. After that, they were taken out and placed in the sheet resistance test fixture (test diameter 2 cm). The four-probe method of the electrochemical workstation was used to test the resistance of the four diaphragms at 25℃. The resistance values ​​of the four diaphragms were obtained by placing them in the fixture one after another. Then, the average resistance value of the four diaphragms was taken, and the average resistance value was multiplied by the test area of ​​the diaphragm (3.14 cm²). 2 ), that is, the surface resistance (Ω•cm) is obtained. 2 ).

[0128] (3) Electrolytic cell voltage: The electrolysis is carried out under normal pressure and constant temperature of 80℃, using 30 wt% KOH aqueous solution as electrolyte, Raney nickel as cathode catalyst and porous nickel as anode catalyst, and the anode and cathode are isolated by a composite diaphragm; the electrolysis chamber is controlled at 5000 A / m 2 The constant current density is constant current operation. After the operating conditions stabilize and the voltage fluctuation is stable, the steady-state working voltage of the electrolysis chamber is collected and recorded. The test is repeated three times and the average value is taken to obtain the standard working voltage under this condition.

[0129] (4) Stability: The stability of the composite diaphragm is characterized by the change (reduction rate) of the bubble point before and after 500h of circulation; specifically: reduction rate = 100% × (bubble point before tanking - bubble point after tanking) / bubble point before tanking; the bubble point test method is to inject water into one side of the composite diaphragm and pressurize the other side with compressed air at a speed of 2 bar / min to observe the generation of bubbles. The pressure of the first bubble is the bubble point value of the composite diaphragm.

[0130] The specific test results are shown in Table 1.

[0131] Table 1 As shown in Table 1, the composite diaphragm provided by the present invention, by controlling the mass ratio of the first polymer, inorganic material and substrate within a specific range, and controlling the roughness of the first surface within a specific range, enables the composite diaphragm to achieve low sheet resistivity, high mechanical strength and excellent cycle stability, and can reduce the electrolytic cell voltage; the tensile strength of the composite diaphragm is 8~40MPa, and the sheet resistivity is 0.161~0.183Ω•cm. 2 The electrolytic cell voltage is 1.70~1.85V, and the bubble point reduction rate is 8~31% after 500h of circulation.

[0132] As can be seen from the comparison of Comparative Examples 1 and 2 with Example 1, the roughness of the first surface is not within a specific range, and at least one of the composite membrane’s surface resistance, electrolytic cell voltage, and stability deteriorates.

[0133] As can be seen from the comparison of Comparative Examples 3 and 4 with Example 1, when the mass ratio of the first polymer, inorganic material and substrate is not within a specific range, at least one of the tensile strength, sheet resistance, electrolytic cell voltage and stability of the composite membrane deteriorates.

[0134] The applicant declares that the above description is only a specific embodiment of the present invention, but the protection scope of the present invention is not limited thereto. Those skilled in the art should understand that any changes or substitutions that can be easily conceived by those skilled in the art within the technical scope disclosed in the present invention fall within the protection and disclosure scope of the present invention.

Claims

1. A composite diaphragm, characterized in that, The composite membrane comprises a first polymer, an inorganic material, and a substrate, wherein the mass ratio of the first polymer, the inorganic material, and the substrate is (40~75):(120~175):1; and the composite membrane has a first surface and a second surface disposed opposite to each other, wherein the roughness Ra of the first surface is 0.5~15μm.

2. The composite diaphragm according to claim 1, characterized in that, The roughness Ra of the first surface is 3~8μm; Preferably, the first surface is provided with a strip-shaped protrusion structure, which is straight or wavy.

3. The composite diaphragm according to claim 1 or 2, characterized in that, The first surface satisfies at least one of the following: (a) The distance between any two adjacent strip-shaped protrusions on the first surface is independently 30~100μm; (b) The width of the strip-shaped protrusions in the first surface is 1~50μm; (c) The height of the strip-shaped protrusions in the first surface is 10~50μm; (d) The strip-shaped protrusions in the first surface are wavy, with the distance between the crests and troughs being 20~100μm.

4. The composite diaphragm according to claim 1, characterized in that, The substrate is a sulfonated substrate, and the degree of sulfonation of the sulfonated substrate is 5~15%.

5. The composite diaphragm according to any one of claims 1 to 4, characterized in that, The density of the substrate is 1.3~1.36 g / cm³. 3 ; Preferably, the tensile elongation of the substrate is 10-50%; Preferably, the tensile modulus of the substrate is 1000~3000 kgf / cm². 2 ; Preferably, the thickness of the substrate is 240~300μm.

6. The composite diaphragm according to any one of claims 1 to 5, characterized in that, The first polymer includes at least one of polysulfone, polyethersulfone, polyphenylene sulfone, and polyetheretherketone; Preferably, the inorganic material includes at least one of zirconium dioxide, titanium dioxide, barium sulfate, and barium zirconate; Preferably, the substrate comprises at least one selected from polyphenylene sulfide, polypropylene, polytetrafluoroethylene, polyvinylidene fluoride, polyethylene terephthalate, polybutylene terephthalate, polyacetal, polyamide, polycarbonate, polyimide, polyetheretherketone, polyethersulfone, polyphenylene ether, and polyethylene naphthalate. Preferably, the thickness of the composite diaphragm is 390~520μm.

7. A method for preparing a composite separator according to any one of claims 1 to 6, characterized in that, The preparation method includes the following steps: (1) Provide a substrate and lay the substrate flat and fix it on one side of the polydimethyloxane template; (2) Prepare a coating slurry and coat the coating slurry onto a surface of the substrate away from the polydimethylsiloxane template. Then, the substrate is subjected to pre-evaporation, phase inversion, and peeling of the polydimethylsiloxane template to obtain the composite membrane.

8. The preparation method according to claim 7, characterized in that, The coating slurry comprises, by weight percentage, 5-15% of a first polymer, 20-40% of inorganic materials, 0.5-2% of a second polymer, and 45-70% of organic solvents; Preferably, the second polymer comprises a hydrophilic polymer, preferably at least one of polyvinylpyrrolidone, polyvinyl alcohol, and polypropylene glycol; Preferably, the organic solvent includes at least one selected from N-methylpyrrolidone, N,N-dimethylformamide, dimethyl sulfoxide, and diethyl sulfoxide; Preferably, at 25°C, the viscosity of the coating slurry is 3000~10000cp.

9. The preparation method according to claim 7 or 8, characterized in that, Step (1) also includes the step of sulfonating the substrate; Preferably, the reagent for the sulfonation treatment in step (1) includes fuming sulfuric acid; Preferably, the mass ratio of the substrate to the volume ratio of fuming sulfuric acid is 1 g:(4~6) mL; Preferably, based on the total mass of the fuming sulfuric acid as 100%, the mass percentage of free SO3 in the fuming sulfuric acid is 15-25%; Preferably, the sulfonation temperature in step (1) is 15~25℃ and the sulfonation time is 0.2~0.6h; Preferably, the pre-evaporation temperature in step (2) is 50~110℃ and the time is 1~5min; Preferably, the phase transformation time in step (2) is 0.5~3h; preferably, the peeling rate of the polydimethylsiloxane template in step (2) is 1~10m / min, and the peeling force is 1~5N / cm. 2 .

10. An alkaline water electrolysis device, characterized in that, The alkaline water electrolysis device includes at least one of the following: (1) The composite diaphragm according to any one of claims 1 to 6; (2) The composite diaphragm prepared by the preparation method according to any one of claims 7 to 9.